Impact of stroke volume on cardiovascular risk during progression of aortic valve stenosis. Issue 18 (28th April 2017) - Lønnebakken, Mai Tone; De Simone, Giovanni; Saeed, Sahrai; Boman, Kurt; Rossebø, Anne B; Bahlmann, Edda; Gohlke-Bärwolf, Christa; Gerdts, Eva
Abstract : Objective: In severe aortic valve stenosis (AS), low left ventricular (LV) stroke volume has been associated with increased cardiovascular (CV) mortality, but this association has not been explored during progression of AS in a large prospective study. Methods: In 1671 patients from the Simvastatin Ezetimibe in Aortic Stenosis (SEAS) study, the association of stroke volume indexed for body surface area (SVI) with major CV events during a median of 4.3-year follow-up was assessed in Cox and time-varying Cox regression analyses. Low SVI was defined as <35 mL/m 2 . Results: Peak aortic jet velocity in the total study population was 3.1 ±0.7 m/s. Low SVI was found in 23% at baseline and associated with higher age, body mass index (BMI), heart rate and global LV load, and with lower mean aortic gradient, aortic valve area index, energy loss index, LV mass and ejection fraction and more often inconsistent AS grading (all p<0.05). A 5 mL/m 2 lower SVI at baseline was associated with higher HRs of major CV events (n=544) (HR 1.09, 95% CI 1.05 to 1.13, p<0.001) and higher total mortality (n=147) (HR 1.08, 95% CI 1.01 to 1.16, p=0.038), independent of age, sex, atrial fibrillation, mean aortic gradient, LV ejection fraction, LV mass, BMI and study treatment. Adjusting for the same covariates, low SVI at baseline and in-study low SVI were also associated with increased rate of major CV events. Conclusion: In patients with AS in the SEAS study, lower baseline SVI was associated with higher HR of major CV events and total mortality independent of major confounders. Trial registration number: NCT00092677: Results